Some problems of interpretation of normative legal acts of civil legislation (from D.I. Meyer until nowadays) - V.N. Koval (Ученые записки Казанского университета: Серия Гуманитарные науки, 2019)
The paper describes the problems of interpretation of normative legal acts. The situation when court decisions are defined by the non-normative sources, as well as by the normative sources that do not apply to the judicial matter, has been considered. It has been revealed that the modern legal science often uses reference sources to interpret the legal provisions. The aspects of morphological, syntactical, and logical interpretation of the civil legislation acts have been investigated. The specifics of using the static and dynamic interpretation have been discussed. Thus, the common grounds (principles) of the legislation have been singled out. Based on the obtained results, it has been concluded that the problem of interpretation of normative legal acts, which was urgent in D.I. Meyer's times, is still relevant. The tasks of correct law interpretation set in the 19th – 20th centuries have not been fulfilled. Therefore, it has been suggested to define the rage of the most important tasks, to determine the vector of scientific and empirical studies, to draft the stages, and to find the efficient technique for achieving the success in solving the issue.